Branding Strategies for Competitive Advantage: A Study of the Malaysian Banking Sector - Yoon, Alice Chee Mun (2007)
“The objective of strategy is a sustainable competitive advantage, which may come from any part of the organisation's operation. The market is the judge of this advantage. Brand strategy is the process whereby the offer is postioned in the consumer's mind to produce a preception of advantage” (Arnold, 1992)